Cerebral strokes with coronavirus infection (Eurasian Medical Research Periodical, 2023)
The main mechanisms of penetration of a new coronavirus infection into the central nervous system, risk factors for the development and forms of cerebral vascular complications, are considered, and their own clinical observation is described. Key words: coronavirus disease, vascular risk factors, neurological complications, strokes.